The place of lions - Campbell, Eric (Eric M.) (San Diego : Harcourt Brace Jovanovich, 1991)
When the plane flying Chris and his father crashes on the Serengeti Plain, Chris sets out to find help and finds that his journey is paralleled by that of an aging lion.
"First published 1990 by Macmillan Children's Books London"--T.p. verso.
Notable/Best Books (A.L.A.).
Publisher's Weekly.
School Library Journal.
Book Report, June 2007.
Booklist, September 2007.
Keywords: Aircraft accidents -- Fiction; Lions -- Tanzania -- Fiction; Survival -- Fiction; Aeronautics -- Accidents -- Fiction; Lions -- Fiction; Survival after airplane accidents, shipwrecks, etc; Serengeti Plain (Tanzania) -- Fiction; Serengeti Plain (Tanzania) -- Fiction